Curing Effect and Resistivity Evolution of Zinc-Contaminated Red Clay Cured by Phosphate-Based Binder - Yu Song; Xiaohui Gan; Hui Li; Mingzhi Zhang; Mingming Xue; Xiaotong Gao; Jun Li (Geofluids)
Curing agent is often used in the in situ remediation of industrial contaminated sites. The reaction between curing agent and contaminated soil has a great impact on the conductivity of soil. Quantitative analysis of the resistivity evolution of cured contaminated soil is an important prerequisite for the accurate evaluation of the in situ remediation effect of heavy metal contaminated sites. In this paper, the pH value, unconfined compressive strength, and resistivity evolution of Zn-contaminated red clay cured with new phosphate-based binder (KMP) at different curing ages were tested, and the internal relationship between the KMP content and the metal ion content and the pH value, unconfined compressive strength, and resistivity evolution were analyzed. The curing effect of KMP, Zn2+ concentration, and curing age on contaminated soil was further evaluated. The results show that the unconfined compressive strength of red clay is weakened with the increase of Zn2+ concentration. The curing effect of KMP on zinc-contaminated red clay is obvious. The pH control of KMP curing agent on zinc-contaminated red clay is effective, and the pH value within 10.5 can effectively stabilize metal ion leaching. There is a good linear relationship between KMP content and curing age and resistivity. Under uniaxial compression, the resistivity decreases with the increase of stress at different Zn2+ concentrations, and the minimum value of the resistivity corresponds to the peak value of uniaxial compression. It provides possibility for the application of resistivity method in the study of mechanical strength properties of red clay.